Characteristics Analysis and Optimum Design of Small Size Thrust Air Bearing for HDD - Parametric Study - Ibrahim, M.D; Namba, T.; Ochiai, M.; Hashimoto, H. (2008)
Grooved thrust air bearings are widely used for very high speed and lightly loaded machinery. The revolutionary spin is relatively extremely high and is very applicable to meet future expectation because of their low friction, low operational noise and environmentally friendly. With the country's aim in increasing the HDD storage capacity, eventually it will lead to higher revolutionary HDD bearing. Currently HDD bearings depend on hydrodynamic oil bearings. To cope with the increasing of storage capacity demand, higher revolutions of bearing will become necessary; hence oil-lubricated bearing will face its major problem, which is high friction torque and bearing stiffness reduction. As a substitution, the thrust air bearing has been highly expected to be the next new version of high revolutionary bearings. However the stiffness of thrust air bearing is relatively weak and it is important to improve the bearing stiffness to fully utilize the air-lubricated bearing. This paper shows the possibility of the new version of air-lubricated bearings to be exchanged with the conventional oil-lubricated bearings by showing the comparison applied for HDD.